An investigation on wear loss and hardness of nitro-carburizing coated stainless-steel grade-316. (2022) - Jeyakymar, M.; Munusami, V.; Shanmugam, P.; Boopalan, N.; Boopathi, Sampath; Sureshkumar, M.
Abstract: In this article, the wear loss and hardness of nitrocarburizing coated Stainless-steel grade-316 have been investigated using Taguchi's design of experiments. The percentage of cyanate (CNO–) in the nitrocarburizing solution, nitrocarburizing temperature, and nitrocarburizing time have been used as process parameters to optimize the wear loss and hardness of the coated surface. The stainless-steel grade-316 has been used to make the various medical components due to its good mechanical and chemical properties. The best processes parameter settings for minimizing wear loss and maximizing surface hardness have been predicted by Taguchi analysis. The effects, significant parameters, and the contribution of each parameter to the responses have been examined. It was observed that the nitro-carburizing solution should have 35% of Cyanate, 590˚C of temperature with 135 min of process time is recommended for maximizing hardness (246.22 Hv) and minimizing the wear loss (0.071 cm 3 ) of the coated stainless-steel grade-316. The microstructure of the worn-out coated surface has been illustrated through Scanning electron microscope (SEM) analysis.